Mediator role of presence of meaning and self-esteem in the relationship of social support and death anxiety - Huang, Yuxin; Guan, Ziyao; Yan, Fang; Wiley, James A.; Reynolds, Nancy R.; Tang, Siyuan; Sun, Mei (Frontiers in Psychology, 2022)
Death anxiety has increased following the COVID-19 pandemic. Although Terror Management theory has suggested social support, presence of meaning and self-esteem functioned as death anxiety buffers, few existing works have explored the mechanism of how social support, presence of meaning, and self-esteem buffer death anxiety. To identify these mechanisms is the aim of this study. Our cross-sectional study was conducted with 1167 people in China from 19 May 2020 to 1 June 2020 during the COVID-19 outbreak. The average age of participants was 26 years. Data were by questionnaire, including demographic information, the Templer's Death anxiety scale, the multidimensional scale of perceived social support, the presence of meaning scale, and the Rosenberg self-esteem scale. Results, using structural equation modeling, showed presence of meaning and self-esteem fully mediated the relationship between social support and death anxiety, respectively and sequentially. Overall, our findings demonstrate significant mediator roles of presence of meaning and self-esteem in the relationship of social support and death anxiety. Multi-component interventions are needed to manage death anxiety by targeting increasing social support, presence of meaning and self-esteem and increasing presence of meaning and self-esteem when social support is diminished in the pandemic.